Polygonum istanbulicum Keskin sp nov (Polygonaceae) from Turkey - (:unkn) unknown (WILEY, 2009)
A new Polygonum L. species, P. istanbulicum Keskin, is described from the Istanbul province of Turkey and is compared with other allied species. In addition, an updated list of all Polygonum (s. l.) species recorded from Turkey is provided.